Upplevelser av stress - att jämföra lön och kärriärmöjligheter med nära arbetskamrater (Sociologisk Forskning, 2005)
In this article, relations between social comparisons and experiences of stress are studied. The comparison referent is close workmates and the comparison attributes are salary and career opportunities. Different mediating processes have been extracted from theories of socialcomparisons, reference groups and inequity. The comparison processes are contextualised through social class, in accordance with the Erikson and Goldthorpe class scheme. Data were collected 2003 through a postal survey to employees in Sweden (n=32 86). To be in a situation with worse salary than close workmates are related to experiences of stress for employees in intermediate class positions, and this can be seen as a consequence of relative deprivation. Another result is that for employees in working class positions, a relationship is found between worse career opportunities and experiences of stress.
Keywords: justice; relative deprivation; social class; social comparisons; stress.